2010
DOI: 10.1111/j.1440-1746.2009.06084.x
|View full text |Cite
|
Sign up to set email alerts
|

Four hundred and twenty‐three consecutive adults piggy‐back liver transplantations with the three suprahepatic veins: Was the portal systemic shunt required?

Abstract: This experience indicates that our approach is feasible with a low specific risk and can be performed without portacaval shunt, with minimal outflow venous complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 26 publications
(43 reference statements)
2
12
0
Order By: Relevance
“…First, in the March issue of the Journal of Gastroenterology and Hepatology, our group from Strasbourg reported a large series of 423 consecutive adult piggyback liver transplants with the 3 suprahepatic veins. 3 The technique and the intraoperative view reported in this article are quite similar. Furthermore, our anastomosis also allows optimal venous drainage of the graft and can be created with partial clamping of the native inferior vena cava.…”
supporting
confidence: 56%
“…First, in the March issue of the Journal of Gastroenterology and Hepatology, our group from Strasbourg reported a large series of 423 consecutive adult piggyback liver transplants with the 3 suprahepatic veins. 3 The technique and the intraoperative view reported in this article are quite similar. Furthermore, our anastomosis also allows optimal venous drainage of the graft and can be created with partial clamping of the native inferior vena cava.…”
supporting
confidence: 56%
“…Currently, transplant outflow obstruction by kinking, stenosis or thrombosis of the inferior vena cava (IVC) or hepatic vein, especially in LDLT, are relatively un common complications following liver transplantation with an reported incidence of less than 3% [94,95] (Table 8 and Figure 5). Clinical presentation ranges from lower limb edema, hepatomegaly, ascites, pleural effusions, BuddChiari syndrome, liver and renal failure to hypotension leading to allograft loss and multiorgan failure [4,89,135] .…”
Section: Caval Vein Complicationsmentioning
confidence: 99%
“…The preservation of the recipient IVC with the PB technique has been associated with an increased risk of suprahepatic IVC thrombosis or stenosis, leading to acute or chronic BuddChiari syndrome in 0% to 1.6%, venous congestion of the liver allograft in 1%, and with an increased incidence of posttransplant ascites [89,135] . To avoid such complications, techniques for optimizing outflow with the piggyback technique have been described; the main of these in undoubtfully the width of the caval anastomosis, while other authors have reported methods using either the twovein or the threevein technique for anastomosis with a low rate of CACs [89,94,135,145149] . Finally, several studies have demonstrated the superiority of modifiedPB with the threehepatic vein technique, which should be routinely used in OLT because it is safe and efficient and invo lves few surgical complications [89,94,143] .…”
Section: Caval Vein Complicationsmentioning
confidence: 99%
See 2 more Smart Citations